Legal Reconstruction of the Legality of Digital Telemedicine in the Health Industry - Rene Zakharia Pongsilurang; Hono Sejati; Wieke Dewi Suryandari (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The emergence of telemedicine as a digital transformation in the healthcare industry is a remarkable innovation that merges cutting-edge technology with community involvement. The progress has been found to enhance the quality of healthcare services but also poses challenges to ethical values in medicine that must be upheld to safeguard human dignity. Consequently, there is a pressing need to reform laws that can safeguard both healthcare providers and patients. Suggested legal reforms include modifying medical practice regulations to ensure equitable legal protection for doctors and patients during telemedicine consultations and bolstering the use of medical records as evidence in conflict resolution. These measures are aimed at ensuring that technological advancements in healthcare align with the values of Pancasila, which prioritize scientific values, fairness, justice, humanity, and balance, as well as the safety and protection of patients.